Using PLUS-InVEST-OPGD model to explore spatiotemporal variation of ecosystem carbon storage and its drivers in Jinsha river basin, China - Lichang Huang; Xue Ding; Jinliang Wang; Shuangyun Peng (PeerJ, 2025)
Land-Use/Land-Cover Change (LUCC) is a key disturbance factor of the carbon cycle in terrestrial ecosystems, and the study on the coupling mechanism between LUCC and carbon storage is of great scientific value for implementing a regional carbon-neutral strategy. In this study, the Jinsha River Basin in Yunnan Province, which has outstanding ecological vulnerability, is taken as the research object, and a synergistic analytical framework of “spatial and temporal pattern drivers” is constructed by integrating multi-temporal remote sensing data and multi-model coupling method. Based on the high-precision 30 m land use data from 1990 to 2020, the PLUS-InVEST-OPGD multi-model coupled system was used to simulate and predict the characteristics of spatial and temporal carbon storage differentiation in 2030 under four development scenarios, namely, natural development (ND), ecological protection (EP), farmland protection (FP), and economic development (ED), and to analyze the driving mechanism using the Optimal Parameter Geodetic Probe (OPGP). The driving mechanism is analyzed using an optimal parameter geodetector. The main findings were: (1) The land use structure of the watershed in the study area showed a significant ecological-productive dichotomy, with forest land (60.58%), grassland (28.85%) and cultivated land (7.19%) constituting the core carbon sink carriers (the average proportion of which was 96.62% from 1990 to 2020). Still, the area of forest and grassland decreased by a total of 2,757.84 km2 in the past 30 years, and the expansion of construction land amounted to 2,321.91 km2; (2) the spatial and temporal evolution of carbon storage shows the heterogeneous characteristics of “overall decreasing and local optimization”, in which the carbon loss from forest to grassland conversion is as high as 30% of the total carbon loss, and the expansion of construction land leads to irreversible decay of carbon sinks of about 50%; (3) a multi-scenario simulation shows that the EP scenario minimizes the loss of carbon storage (−2.46 × 106 t) by maintaining a 96.82% ecological land share in 2030, reducing the carbon deficit by 7.79 × 106 t compared with the ND scenario; (4) the average annual temperature is the largest single factor affecting carbon storage, and its interaction with the population factor has a high q value of 0.84. This study innovatively reveals the nonlinear threshold effect of LUCC-carbon storage response in the Jinsha River Basin of Yunnan Province, and the proposed optimization model of “ecological protection” can provide decision support and corresponding reference for the construction of ecological security barriers in the upper reaches of the Yangtze River.